PENERAPAN LEAN SUPPLY CHAIN UNTUK MENINGKATKAN EFISIENSI RANTAI PASOK: STUDI KASUS PADA INDUSTRI PENGOLAHAN KARET - Affandi, Nurul; Lawi, Ansarullah; Septiana, Reski (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
The rubber industry is an important sector that processes, produces, and utilizes products made from rubber materials, with natural rubber sap as the primary raw material. The industry faces challenges such as mismatched rubber receipt data, which affects production targets due to supply chain disruptions. This study aims to implement Lean Supply Chain at PT A and estimate the efficiency of its application in meeting production goals. The research applies Lean Supply Chain principles to identify and eliminate waste in the supply chain of PT A, from harvesting to storage, using Value Stream Mapping (VSM). The identified waste includes environmental impact, product defects, waiting times, underutilized talent, transportation inefficiencies, excessive movement, and over-processing. Root causes of waste are analyzed using Fishbone Diagrams and the 5 Whys method, followed by corrective actions that align with the identified root causes. The activity mapping process resulted in a 3% increase in production efficiency for Ribbed Smoked Sheet (RSS). Furthermore, Lean Supply Chain implementation reduced rubber processing time from 8 days to 5 days, as per VSM analysis. This study provides valuable insights into how Lean Supply Chain can enhance efficiency and production in the rubber industry.